Rearing mice at 22°C programs increased capacity to respond to chronic exposure to cold but not high fat diet - Daniele Neri; Angela M. Ramos-Lobo; Seoeun Lee; Alexandre Lafond; Lori M. Zeltser (Molecular Metabolism, 2023)
Objective: Rodent models raised at environmental temperatures of 21–22 °C are increasingly switched to thermoneutral housing conditions in adulthood to better capture human physiology. We quantified the developmental effects of rearing mice at an ambient temperature of 22 °C vs. 30 °C on metabolic responses to cold and high fat diet (HFD) in adulthood. Methods: Mice were reared from birth to 8 weeks of age at 22 °C or 30 °C, when they were acclimated to single housing at the same temperature for 2–3 weeks in indirect calorimetry cages. Energy expenditure attributable to basal metabolic rate, physical activity, thermic effect of food, and adaptive cold- or diet-induced thermogenesis was calculated. Responses to cooling were evaluated by decreasing the ambient temperature from 22 °C to 14 °C, while responses to HFD feeding were assessed at 30 °C. Influences of rearing temperature on thermogenic responses that emerge over hours, days and weeks were assessed by maintaining mice in the indirect calorimetry cages throughout the study. Results: At an ambient temperature of 22 °C, total energy expenditure (TEE) was 12–16% higher in mice reared at 22 °C as compared to 30 °C. Rearing temperature had no effect on responses in the first hours or week of the 14 °C challenge. Differences emerged in the third week, when TEE increased an additional 10% in mice reared at 22 °C, but mice reared at 30 °C could not sustain this level of cold-induced thermogenesis. Rearing temperature only affected responses to HFD during the first week, due to differences in the timing but not the strength of metabolic adaptations. Conclusion: Rearing at 22 °C does not have a lasting effect on metabolic adaptations to HFD at thermoneutrality, but it programs an enhanced capacity to respond to chronic cold challenges in adulthood. These findings highlight the need to consider rearing temperature when using mice to model cold-induced thermogenesis.